Exploring new training scenarios: 17 years of external rotations in Family and Community Medicine and Nursing at the Huesca Teaching Unit. - Aller Blanco, Ana Isabel; Loscertales Artieda, María Isabel; Lorés Casanova, Soledad; Mendoza Escuer, Ana Isabel (Spanish Journal of Medical Education, 2025)
Objective: To analyze the external rotations carried out by MIR and EIR residents of the Multidisciplinary Teaching Unit of Huesca between 2008 and 2024, reviewing destinations, duration, evaluation, motivations, training impact, barriers and recommendations. Methods: Study design: Descriptive, retrospective and cross-sectional study with a mixed approach (quantitative and qualitative) at the Multidisciplinary Teaching Unit of Huesca. Participants: 91 external rotations managed since 2008, of which 54 (59.3%) were carried out between 2022 and 2024. Twenty-one responses were received to the survey sent to residents who completed rotations in the last four years. Interventions: Data collection through internal records, evaluation reports and a self-administered survey. Variables such as type of center, location, evaluation, presentation of the experience, motivations, barriers and perception of the impact were analyzed. Main measurements: Dichotomous and multi-category qualitative variables, ordinal variables (Likert scale), and open-ended questions were analyzed using statistical tools and thematic analysis. Results: A significant increase in demand for external rotations was observed after the pandemic. Most were national, with a preference for hospitals. South America was the most popular international destination. Personal interest was the main reason. 95% rated the training impact as high or very high, 85% had no difficulties managing it, and 100% would recommend the experience. Conclusions: Since 2020, external rotations have increased, especially for IRTs, with a preference for Aragon and South America. Although dissemination was limited, the perception of the training impact was high. Areas for improvement have been identified regarding the involvement of Teaching Units and tutors in preparation, supervision, and dissemination.